Scorpions (Arachnida, Scorpiones) at elevated altitudes of an area of conservation in the Caatinga - Souza, Phelipe Rêgo Lisboa de; Benati, Kátia Regina; Peres, Marcelo Cesar Lima (Ciência e Natura, 2020)
This study aims to report the diversity of scorpions at elevated altitudes in the Parque Estadual das Sete Passagens (PESP), in an area of conservation located in the Chapada Diamantina within the Caatinga domain in north-eastern Brazil. Data collection occurred in December 2016 and December 2017, through the use of pitfall traps and nocturnal manual collection with the help of ultraviolet torches. 86 individuals were collected, pertaining to nine species, grouped into two families. The Bothriuridae represented 71% of samples, with Bothriurus sp. 1 occurring at all sample altitudes. Whereas, the Buthidae represente 29% of samples, with Ananteris sp, the most represented species, occurring at altitudes of 1,000m and 1,076m and Tityus stigmurus inhabiting areas with extensive human presence. The ample diversity found in the PESP, reveals that this location can be considered representative of the scorpiofauna of Bahia and of the Caatinga, especially due to the lack of data available on scorpions in semi-arid environments.